Acts of Improvement: On the Use of Tonics and Elixirs in Sanskrit Medical and Alchemical Literature - Wujastyk, Dagmar (History of Science in South Asia)

(untitled) (University of Alberta Library, 2017)
In Sanskrit medical literature, rasāyana is defined as one of eight subject areas of medicine. The proclaimed aim of rasāyana therapies is to preserve or promote health and well-being, but also to prolong life, to halt degeneration caused by aging, to rejuvenate and to improve cognitive function. The term “rasāyana” describes the therapies that together constitute this branch of medicine; the methodology and regimen of treatment; and the medicinal substances and formulations used in these therapies.In Indian alchemical literature, the Sanskrit term “rasāyana” is predominantly used to describe the final stages of alchemical operations, i.e. all that is involved in the taking of elixirs for attaining a state of spiritual liberation in a living body. Rasāyana in this sense describes a series of related processes, including the preparation of the elixir; the preparation of the practitioner; the intake of the elixir and finally, the process of transformation the practitioner undergoes after intake of the elixir.In my paper, I present examples of rasāyana sections from a selection of medical and alchemical treatises to explore their connections and divergences. I also discuss how the connections between medical and alchemical rasāyana sections reflect the development of iatrochemistry in alchemical literature.